Short-windedness Would Weaken Effective Climate Policy - Wilfried Rickels; Sonja Peterson (Environmental and Resource Economics, 2020)
Most states have implemented quite strict measures designed to slow down the spread of the coronavirus among their populations. For most sectors, these measures have resulted in a significant reduction of economic activity, output, and hence also output-related emissions. Commitment to these measures, apparently regardless of the economic costs involved, is considered by some people to be a blueprint for the commitment required to mitigate climate change and to achieve the Paris climate targets. However, when it comes to devising an efficient climate policy, the differences between the two crises—cororonavirus and climate change—need to be taken more seriously than the similarities. Alarming have been the various calls to put a quick end to corona prevention measures and the restrictions they place on public and economic activity, indicative as they are of the priority accorded to high discount rates and the absence of precautionary thinking among policy-makers. Both the differences between the two crises themselves and the similarities in the reluctance to focus on achieving (more) long-term benefits emphasize once again the need for long-term commitment to climate policies in line with agreed targets.
Keywords: 330; climate policy; carbon prices; economic recovery; corona virus; lock-down